Diversity of sate (satay) as Indonesian ancient food - L. Rahmah; N. I. P. I. Sari; A. N. M. Ansori (Теория и практика переработки мяса, 2024)
Sate (satay) dishes have a wealth of ingredients and spices spread throughout Indonesia, which produces a diversity of types and flavors of satay. In sate dishes, the way pieces of meat are served on skewers was affected by Arabic culture, which influence is most visible in the development of Indonesian food culture. On average, sate is made using grilling, which is an ancient type of cooking technique survived into modern times. For centuries, wood and charcoal have been some of the oldest human-made fuels as important ingredients for cooking and heating in ancient times and even today. Apart from being an everyday food, sate is Indonesia’s gastronomic culinary cultural heritage with a wide diversity that needs to be preserved because it functions as a national identity and has excellent potential for developing culinary tourism.